Studies on the Biochemical Composition of the Whole, Flesh and Exoskeleton of Two Penaeid Species from Makoko Fish Landing Sites, of the Lagos Lagoon, South-West Nigeria - Akinwunmi, Mosunmola F.; Okojie, Laura M.; Shonibare, Kehinde B. (Aceh Journal of Animal Science, 2025)
Shrimps remain a healthy seafood option found in most recipes of people all over the world due to its rich supply of protein, vitamins and minerals. With this and several reasons, it becomes pertinent for consumers to be informed on the choice of the parts of the shrimps they eat. This study therefore, sought to examined the morphometric characters and the biochemical composition of the whole, flesh and exoskeleton of P. monodon and P. longirostris from Lagos Lagoon. Using standard methods, the species were collected monthly between November, 2022 and February, 2023 and later subjected to various laboratory procedures. The morphometric characters showed that P. monodon is larger than P. longirostris with the total length ranging from 11.00 - 20.00 cm, 8.00 - 14.00 cm, total weight ranged between 9.10 - 30.40 g, 5.70 - 15.50 g (before de-shelling) and 5.60 -15.80 g, 3.20 - 6.00 g (after de-shelling) for P. monodon and P. longirostris respectively. The proximate composition varied significantly (p0.05) in both species for the whole body, flesh and the exoskeleton. The flesh of the species contained the highest amount of moisture (7.91, 7.62 %), crude protein (44.01, 45.63 %) and crude fat (1.12, 1.59 %) while the exoskeleton had the highest amount of crude fibre (0.30, 0.23 %), total ash (36.62, 33.82 %) and total carbohydrate (40.87, 41.20 %) for P. monodon and P. longirostris respectively. The minerals analysis indicated that the exoskeleton of the two species had the highest mineral contents with Calcium been the highest (20.580.06 g/100g, 18.920.11 g/100g) of all the minerals for P. monodon and P. longirostris respectively. Based on this nutritional composition, the various parts of both species are recommended for consumption by all human age groups depending on individual preference. The exoskeleton and the shrimp head which are often considered as waste from shrimp processing could serve a potential alternative for industries engaged in animal feed formulation. It is therefore pertinent to pay attention to shrimp nutritional composition which will be of importance to shellfish biologist and aquaculturist during the feed formulation.